The Effect of Colchicine onGenome Size and Agronomical Traits and Correlation with Sugarcane Putative Mutants Production - Nurya Yuniyati; Trikoesoemaningtyas Trikoesoemaningtyas; Sri Suhesti (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
The mutation could improve plant genetic variability. Some putative sugarcane mutants originating from the PS 881 variety have been produced through mutation induction using colchicine. The study aimed to determine the effect of colchicine induced on genome size and agronomical traits, and its correlation with sugarcane putative mutants production. The experiment was conducted at the UPBUP of IAARD, Bogor, July 2018-April 2019. The research was carried out in an augmented design in randomized complete block design, using 35 genotypes of the first generation G0 (30 putative mutants from colchicine 0.03 and 0.05%, five check varieties). The genome size, agronomical traits, i.e. stem number, length, diameter, and weight per meter; internode number and length; brix, and production, were evaluated. This result showed that colchicine increased 5.03-13.64% genome size of putative sugarcane mutants compared to the original variety PS 881. It is significantly different for almost all of agronomical traits. The genome size was significantly correlated very positively with brix and significantly positively with stem length and diameter, and production. Path analysis showed that stem (weight per meter and length) has a direct effect on production, in contrast, genome size, stem diameter, internode number, and brix have an indirect effect through stem weight per meter to production. Indirect selection to obtain high production can be done through stem (weight per meter and length), consider for genome size, stem diameter, internode number, and brix. This is experimental preliminary information, validation on field is needed among direct and indirect of production components to production.Keywords: agronomical traits correlation, colchicine, path analysis, sugarcane production AbstrakPENGARUH KOLKISIN TERHADAP UKURAN GENOM DAN KARAKTER AGRONOMI SERTA HUBUNGANNYA DENGAN PRODUKSI MUTAN PUTATIF TEBUPeningkatan keragaman genetik dapat dilakukan melalui mutasi. Sejumlah mutan putatif tebu yang berasal dari varietas PS 881 telah dihasilkan melalui induksi mutasi menggunakan kolkisin. Penelitian bertujuan untuk mengetahui pengaruh kolkisin terhadap ukuran genom dan karakter agronomi, serta hubungannya dengan produksi mutan putatif tebu. Percobaan dilaksanakan di Unit Pengelola Benih Unggul Pertanian (UPBUP), Badan Litbang Pertanian, Bogor, Juli 2018-April 2019. Penelitian menggunakan rancangan augmented dalam rancangan acak kelompok lengkap, dengan 35 genotipe generasi awal G0 (30 mutan putatif tebu hasil perlakuan kolkisin 0,03 dan 0,05%, serta lima varietas pembanding). Karakter yang diamati adalah ukuran genom dan karakter agronomi (jumlah, panjang, diameter, dan bobot batang per meter; jumlah dan panjang ruas; brix; serta produksi). Hasil penelitian menunjukkan perlakuan kolkisin meningkatkan ukuran genom mutan putatif tebu 5,03-13,64% dibandingkan tetua PS 881 dan mengakibatkan perbedaan yang nyata pada hampir seluruh karakter agronomi. Ukuran genom berkorelasi positif sangat nyata dengan brix dan nyata dengan panjang dan diameter batang, serta produksi. Analisis lintas menunjukkan karakter bobot batang per meter dan panjang batang berpengaruh langsung pada produksi, sedangkan karakter ukuran genom, diameter batang, jumlah ruas, dan brix berpengaruh tak langsung pada produksi melalui bobot batang per meter. Seleksi tak langsung untuk mendapatkan produksi tinggi terutama melalui karakter bobot batang per meter dan panjang batang dengan mempertimbangkan karakter ukuran genom, diameter batang, jumlah ruas, dan brix. Hasil penelitian merupakan informasi awal yang memerlukan validasi hubungan pengaruh langsung dan tak langsung komponen produksi terhadap produksi di tingkat lapangan.Kata kunci : analisis lintas, kolkisin, korelasi karakter agronomi, produksi tebu